Penghambatan Ekstrak Etanol Sereh (Cymbopogon citratus (DC) Stapf ) terhadap Produksi Verotoksin Escherichia coli Verotoksigenik - Cepeda, Gino Nemesio; Hariyadi, Ratih Dewanti; Supar, Supar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
Citronella was a spicy plant used as seasoning in Indonesian food. It was reported to have antimicrobial activity. Itsextract in form of volatile oil prepared by distilation can inhibit the growth of some bacteria. The objective of theresearch was to know the inhibition of ethanolic extract of the citronella on growth and verotoxin production ofverotoxigenic Escherichia coli. The assay of antimicrobial activity was done by using broth dilution and verocellassay. The results indicated that minimum inhibitory concentration of extract can inhibit effectively verotoxinproduction of verotoxigenic Escherichia coli.